(untitled) ("Journal "U". Economy. Management. Finance.", 2024)
The article presents the main groups of digital marketing technologies, defines their role in the development of companies and identifies the main trends in the use of these technologies within the framework of the marketing development trajectory from the concept of Marketing 1.0 to the concept of Marketing 6.0. A demarcation line is also drawn between digital technologies, which are actively used in the marketing activities of large companies that have the investment potential to integrate the latest achievements of machine learning and small businesses aimed at achieving high results through the optimal use of digital technologies, based on competencies in the field of digital transformation management.